mikeJW
Mechanical
- May 2, 2003
- 21
I have two expressions for torque with variable inertia. Will someone check out the maths for me please?
Deriving Torque from energy change
Work T.dq = Energy change = d(1/2 w2.J ) q = rads, w = rad/S
d(1/2 w2.J ) d( w2.J )
Torque T = ------------ = ½ ---------
dq dq
= ½ [ w2.dJ/dq + J.dw2/dq ] = ½ w2.dJ/dq + ½ J.dw2/dq
We now need to re-arrange the second part to prove it equals J.a
dw2/dq = d(w.w)/dq = w.dw/dq + w.dw/dq = 2. w.dw/dq
= 2. (dq/dt).(dw/dq) = 2.dw/dt = 2 a
Thus ½ J.dw2/dq = ( ½ J).(2 a) = J . a
So T = J.a + ½ w2.dJ/dq
This agrees with Pro-Mechanica results
Deriving Torque from rate of change of momentum
Torque T = d(Jw)/dt = J.dw/dt + w.dJ/dt
= J.a + w.(dJ/dq).(dq/dt)
= J.a + w.(dJ/dq).w = J.a + w2.dJ/dq
Why is this different?
Deriving Torque from energy change
Work T.dq = Energy change = d(1/2 w2.J ) q = rads, w = rad/S
d(1/2 w2.J ) d( w2.J )
Torque T = ------------ = ½ ---------
dq dq
= ½ [ w2.dJ/dq + J.dw2/dq ] = ½ w2.dJ/dq + ½ J.dw2/dq
We now need to re-arrange the second part to prove it equals J.a
dw2/dq = d(w.w)/dq = w.dw/dq + w.dw/dq = 2. w.dw/dq
= 2. (dq/dt).(dw/dq) = 2.dw/dt = 2 a
Thus ½ J.dw2/dq = ( ½ J).(2 a) = J . a
So T = J.a + ½ w2.dJ/dq
This agrees with Pro-Mechanica results
Deriving Torque from rate of change of momentum
Torque T = d(Jw)/dt = J.dw/dt + w.dJ/dt
= J.a + w.(dJ/dq).(dq/dt)
= J.a + w.(dJ/dq).w = J.a + w2.dJ/dq
Why is this different?